2016
DOI: 10.1002/tcr.201600047
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Quantum Chemical Approaches to Develop Highly Selective Nanocatalysts for CO2‐free Power Circulation

Abstract: Renewable electricity must be utilized to usefully suppress the atmospheric CO concentration and slow the progression of global warming. We have thus proposed a new concept involving CO -free electric power circulation systems via highly selective electrochemical reactions of alcohol/carboxylic acid redox couples. Design concepts for nanocatalysts able to catalyze highly selective electrochemical reactions are provided from both experimental and quantum mechanical perspectives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Figure 4(b) indicates that the amount of hydrogen is considerably enhanced by the inclusion of TiO 2 -II grains and the best electrocatalytic activity for hydrogen evolution is achieved on the sample with 18 wt% TiO 2 -II, whereas the conversion of oxalic acid on the three TiO 2 catalysts seems almost similar. Considering that the energy position of conduction band bottom predominantly influences the electrocatalytic oxalic acid conversion [23][24][25], the observed activities on TiO 2 catalysts for oxalic acid conversion are plausible because the conduction band energy levels are reasonably the same for the three samples. Taken altogether, it is concluded that the presence of some amounts of TiO 2 -II as the second phase in the anatase matrix can improve the electrocatalytic activity for hydrogen evolution, but the best fraction of TiO 2 -II phase for electrocatalytic activity still needs to be optimized in future studies.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…Figure 4(b) indicates that the amount of hydrogen is considerably enhanced by the inclusion of TiO 2 -II grains and the best electrocatalytic activity for hydrogen evolution is achieved on the sample with 18 wt% TiO 2 -II, whereas the conversion of oxalic acid on the three TiO 2 catalysts seems almost similar. Considering that the energy position of conduction band bottom predominantly influences the electrocatalytic oxalic acid conversion [23][24][25], the observed activities on TiO 2 catalysts for oxalic acid conversion are plausible because the conduction band energy levels are reasonably the same for the three samples. Taken altogether, it is concluded that the presence of some amounts of TiO 2 -II as the second phase in the anatase matrix can improve the electrocatalytic activity for hydrogen evolution, but the best fraction of TiO 2 -II phase for electrocatalytic activity still needs to be optimized in future studies.…”
mentioning
confidence: 83%
“…It should be noted that the group of authors recently reported the electrochemical hydrogenation of oxalic acid (divalent carboxylic acid) to produce glycolic acid (monovalent alcoholic compound) and found that the catalytic activity on TiO 2 considerably depends on the crystal structure, i.e. anatase exhibits extremely high reducibility for oxalic acid but rutile does not [23,24]. The difference in catalytic activity was attributed to the reducibility of electrons introduced from electrode to the conduction band bottom of TiO 2 , i.e.…”
mentioning
confidence: 99%
“…OA electroreduction remains a challenging task because it usually proceeds in acidic conditions, and the active catalysts often corrode in acidic media, causing instability. , Current research works on OA electroreduction mainly focus on Ti-based and Pb-based materials (Table S1). ,,, , Owing to poor stability in acidic media, other metal-based materials, especially Ga, are not suitable in OA electroreduction. Although Ti-based catalysts are reported for GC production, they show highly competitive hydrogen evolution reaction (HER) in acidic media, which tremendously affects the performance. ,,, Pb-based catalysts with high HER overpotential could suppress HER, which are suitable in catalyzing OA conversion to GX; however, in long-term electrolysis, Pb adsorbs OA on the surface, toxifying the active sites and leading to reduction of productivity. , Thus, an acid-stable electrocatalyst with low HER performance is critical to OA electroreduction.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have first succeeded in the OX electro-reduction to produce GC by using an anatase-type TiO 2 cathode for OX reduction and a Pt anode for water oxidation. 3,4 Various types of photoanodes have been developed as a water-oxidation catalyst to produce O 2 . We tried to replace the Pt anode to an oxide photoanode and succeeded in GC production from OX under the irradiation of UV-visible light at a bias 0.6 V lower than the theoretical bias potential for OX reduction accompanied with water oxidation, 1.1 V. 5 Furthermore, we performed electric power generation from GC through selective oxidation of GC to OX using a direct GC alkaline fuel cell employing a Pt anode, i.e., no CO 2 emission.…”
Section: Introductionmentioning
confidence: 99%
“…We tried to replace the Pt anode to an oxide photoanode and succeeded in GC production from OX under the irradiation of UV-visible light at a bias 0.6 V lower than the theoretical bias potential for OX reduction accompanied with water oxidation, 1.1 V. 5 Furthermore, we performed electric power generation from GC through selective oxidation of GC to OX using a direct GC alkaline fuel cell employing a Pt anode, i.e., no CO 2 emission. 3,4 Electrochemical OX reduction to produce GC Nanometer-sized TiO 2 with a high specific surface area, which is denoted as porous TiO 2 spheres (PTSs), were prepared by calcination of layered protonated titanate (LPT). 6 A cathode was prepared by applying suspensions of LPT (10 or 20 mg) diluted in methanol (0.2 mL) on Ti foils (2×2 cm).…”
Section: Introductionmentioning
confidence: 99%